Your Information Literacy Practices (YILP): A New Measure of Information Literacy - Kennette, Lynne N.; McIntosh, Elizabeth Aya (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2022)
Post-secondary students bring with them unique skills and knowledge which may affect their learning. Information literacy (IL) is a set of abilities which permits the discovery of information as well as using this information to create new knowledge (Association of College and Research Libraries, 2016). While IL abilities are heralded as important, it is difficult to find a simple measure of information literacy, especially since its conceptualization as a framework (Association of College and Research Libraries, 2016). In this paper, we propose a new online measure of information literacy—Your Information Literacy Practices (YILP)—which aligns with the new framework. We compare it to another published measure of IL and student resourcefulness. Implications and recommendations for its use are discussed.